2016
DOI: 10.1186/s13287-016-0356-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived stem cells suppress hypertrophic scar fibrosis via the p38/MAPK signaling pathway

Abstract: BackgroundHypertrophic scars (HS) generally occur after injury to the deep layers of the dermis, resulting in functional deficiency for patients. Growing evidence has been identified that the supernatant of adipose tissue-derived stem cells (ADSCs) significantly ameliorates fibrosis of different tissues, but limited attention has been paid to its efficacy on attenuating skin fibrosis. In this study, we explored the effect and possible mechanism of ADSC-conditioned medium (ADSC-CM) on HS.MethodReal-time quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 59 publications
1
94
0
2
Order By: Relevance
“…Skin fibrosis is a pathological outcome of various injuries including wound injuries, exogenous‐induced fibrosis and autoimmune skin diseases. There are three fibrosis models, including bleomycin‐induced fibrosis, radiation‐induced fibrosis and excisional‐induced fibrosis . These models are used to detect the effect of stem cells on skin fibrosis.…”
Section: Current Stem Cell Therapy For Tissue Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…Skin fibrosis is a pathological outcome of various injuries including wound injuries, exogenous‐induced fibrosis and autoimmune skin diseases. There are three fibrosis models, including bleomycin‐induced fibrosis, radiation‐induced fibrosis and excisional‐induced fibrosis . These models are used to detect the effect of stem cells on skin fibrosis.…”
Section: Current Stem Cell Therapy For Tissue Fibrosismentioning
confidence: 99%
“…In addition to the above mentioned mechanisms, others include the p38/MAPK pathway, regulation of miR‐let7c and the ER stress pathway . In particular, ER stress has been proven to be linked to post‐operative skeletal fibrosis .…”
Section: Potential Mechanisms Underlying Anti‐fibrosis Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…, and activation of fibroblasts per se may lead to disorganised fibroblast depositions and scar formation(Bainbridge, 2013), attenuation of scar formation following the ASCs therapy might occur due to the effect of ASCs on the function of fibroblasts. With this regard, preclinical studies showed that ASC-conditioned medium decreased collagen deposition and expression of α-smooth muscle actin in hypertrophic scar fibroblasts, resulting in attenuation of scarring (Y Li et al, 2016)…”
mentioning
confidence: 99%
“…Культуральная среда после выращивания МСК жировой ткани подавляет фибротические процессы в глубоких слоях кожи, уменьшаются объем коллагена и формирование рубцовой ткани [2]. МСК пуповинной крови человека снижают выраженность развития соединительной ткани и портальной гипертензии при индуцированном фиброзе печени у мышей и крыс [3,4].…”
unclassified